DNA Release from Polyaziridine Polyplexes Aided by Biomacromolecules: Effect of pH - Bibi, Iram; Shah, Syed Waqar Hussain (Acta Scientiarum. Technology, 2023)
The pH dependence of heparin and dextran sulfate aided release of DNA from its polyplexes with polyaziridine (PA) has been investigated using Quartz crystal microbalance with dissipation monitoring (QCM-D). The acoustic behavior of ternary systems indicated that the DNA decondensation was favored at physiological pH. When pH < 7.4, PA was significantly positively charged and ternary complexation occurred. When pH exceeded 7.4, very small proportion of DNA was released upon heparin addition due to marked reduction in cationic nature of PA. An increase in thickness at the interface due to adsorbed material at pH 9.0 showed the retention of heparin on the surface despite of negligible release of DNA. In terms of PA binding, heparin proved to be a better competitor than dextran sulfate.